2020
DOI: 10.1038/s41467-020-17651-1
|View full text |Cite
|
Sign up to set email alerts
|

SLIT2/ROBO1-signaling inhibits macropinocytosis by opposing cortical cytoskeletal remodeling

Abstract: Macropinocytosis is essential for myeloid cells to survey their environment and for growth of RAS-transformed cancer cells. Several growth factors and inflammatory stimuli are known to induce macropinocytosis, but its endogenous inhibitors have remained elusive. Stimulation of Roundabout receptors by Slit ligands inhibits directional migration of many cell types, including immune cells and cancer cells. We report that SLIT2 inhibits macropinocytosis in vitro and in vivo by inducing cytoskeletal changes in macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 123 publications
(208 reference statements)
1
37
0
Order By: Relevance
“…Disruption of actin or microtubules in DCs with specific inhibitors significantly prevented macropinocytosis ( 38 ). Meanwhile, SLIT2, a Slit protein, was found to inhibit macropinocytosis by opposing cortical cytoskeletal remodeling ( 39 ). Ruffle membrane/lamellipodia form macropinocytic cups, and then form macropinosomes, involving a series of small GTPases and PIs ( Figure 2 .…”
Section: The General Process Of Macropinocytosismentioning
confidence: 99%
“…Disruption of actin or microtubules in DCs with specific inhibitors significantly prevented macropinocytosis ( 38 ). Meanwhile, SLIT2, a Slit protein, was found to inhibit macropinocytosis by opposing cortical cytoskeletal remodeling ( 39 ). Ruffle membrane/lamellipodia form macropinocytic cups, and then form macropinosomes, involving a series of small GTPases and PIs ( Figure 2 .…”
Section: The General Process Of Macropinocytosismentioning
confidence: 99%
“…To determine whether the inhibitory effect of NSlit2 on lipid uptake is mediated by its receptor, Robo-1, we used Robo1N, a soluble N-terminal fragment of Robo-1, known to inhibit binding of Slit2 to Robo-1, thereby blocking any downstream effects [21][22][23] . In the presence of NSlit2, macrophages internalized significantly less oxLDL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Slit2 to Robo-1 can result in inactivation of Rac through the actions of slit-robo GTPase activating proteins, srGAPs 14,34 . Accordingly, we recently demonstrated that murine macrophages express srGAP2, and that exposure of mouse macrophages to Slit2 causes inactivation of Rac in these cells 23 . Our results are also consistent with work demonstrating a key role for Rac-mediated signaling in foam cell formation 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations